The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1159/000339936
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Healing of the Uterine Incision after Cesarean Section: Is It Preventable by Intraoperative Digital Dilatation of the Internal Cervical Ostium?

Abstract: Background/Aims: It was the aim of this study to determine if intraoperative digital dilatation of the closed internal cervical ostium affects the healing of the uterine scar after a cesarean section (CS). Methods: In this randomized, prospective study, 94 term pregnant patients who elected to have a CS were assigned to two groups: intraoperative digital dilatation of the internal cervical ostium (group I, n = 48) or no dilatation (group II, n = 46). Vaginal ultrasound was used to check the integrity of the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…We found 2 previous studies that recruited participants close to CD. 10,20 However, in those studies, the US examination was performed as early as 6e12 weeks after CD. We decided to perform the examinations 6 months after CD because it has been suggested that the cesarean woundhealing process will take at least 6 months.…”
Section: Commentmentioning
confidence: 99%
“…We found 2 previous studies that recruited participants close to CD. 10,20 However, in those studies, the US examination was performed as early as 6e12 weeks after CD. We decided to perform the examinations 6 months after CD because it has been suggested that the cesarean woundhealing process will take at least 6 months.…”
Section: Commentmentioning
confidence: 99%
“…We have done the examination 6 to 12 months after the CD; some other studies had performed earlier examination at 6 to 12 weeks after CD [17,18] . We preferred to do examination at this time because it was suggested that the healing process of cesarean wound takes at least 6 months [10] .…”
Section: Discussionmentioning
confidence: 99%